PEMBERDAYAAN POSYANDU DALAM PENCEGAHAN DEMAM BERDARAH DENGUE - Tatontos, Erlin Yustin; Urip; Kristinawati, Erna (Poltekkes Kemenkes Mataram, 2025)
Tempos Village is one of 11 villages/sub-districts in Gerung District, West Lombok Regency with the highest number of dengue fever cases and some have even died. The number of dengue fever cases in the Gerung Community Health Center working area in 2022 was 43 people with a Larvae Free Rate (ABJ) of 91.1%. The number of dengue fever cases in Tempos village in 2022 is 6 cases with an ABJ of 89%. At the beginning of January 2023, there was 1 case of death in Tempos village. The problem in Tempos village is the lack of knowledge and skills as well as motivation of the target audience, namely Posyandu women and health cadres in Tempos village regarding dengue fever, prevention efforts as well as early treatment of infected residents and vector control with natural ingredients and ABJ < 95%. The solution offered in the implementation of the Community Service (PKM) Community Partnership Program (PKM) for empowering Posyandu in preventing dengue fever in Tempos village in the working area of the Gerung Health Center, West Lombok Regency is with promotive and preventive efforts. The results that have been achieved are the implementation of PKM starting from obtaining permits and observations, socialization and counseling in Tempos village and training at the Gerung Community Health Center. Health cadres can campaign for the use of anti-mosquito plants and larvae-eating fish among mothers at Posyandu. Every Friday village officials together with health cadres and the community carry out 3 M plus activities and the 1 house 1 jumantik movement. To ensure the continuity of the program, anti-mosquito plant seeds have been handed over along with pots, larvae-eating fish seeds and flashlights to be used in larvae surveys to the village which are then handed over to health cadres from Posyandu representatives in each hamlet.